The Important Role and Responsibility of Military Personnel in Ensuring - Ubaydullayevich, Saydullaev Ulugbek; o’g’li, Ibotov Qobiljon Nurilla (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the organization and strengthening of military culture in the military collective, the soldiers’ brotherhood in it. Meetings with scientists, creative figures and artists, outstanding personalities, veterans are of great importance in the aesthetic, spiritual, moral and patriotic education of military personnel. Not only commanding officers, but also all categories of military personnel in ensuring public safety.